Graduate entrepreneurship career choice in Malaysia: determinants and international comparison - Sabirah, Sulaiman (2020)
Entrepreneurship is a powerful force that spurs economic progress of most nations in creating and fulfilling a sustainable economy. In 2019, one out of five Malaysian graduates remained unemployed. These graduates make up 55 percent of those who are unemployed. Moreover, a very low percentage of graduates choose entrepreneurship as their career choice. The integration between TPB (Theory of Planned Behavior) and the economics theories on graduate entrepreneurship career choice could be predicted from the perspective of determinants and international comparison. Previous studies on graduate entrepreneurship career choice were mostly focused on intention, instead of actual choice, even though intention could be substantially different from actual choice. Other research gaps are identified, such as lack of international comparison. This study fills these research gaps via quantitative and qualitative approaches with primary data and international comparison to investigate the different perspective of determinants. Content analysis, descriptive and regression analysis are employed using a sample of 1723 local and 156 international graduates. Findings revealed that university education and language proficiency are unimportant factors for graduates in entrepreneurship career choice. Moreover, the relationship between graduates’ academic achievements and the choice to be an entrepreneur is negative but significant. The views of local and international graduate entrepreneurs differ with regard to entrepreneur choice and role of education, where local graduates see education as not helping them much, while international graduate entrepreneurs view the process of learning is more important than the end result. This study provides new insights on factors affecting career choice as entrepreneurs among graduate. From the economic point of view, the foundation for each of these theories is found to be inter-related and complements each other. Furthermore, the findings give important implications to graduates, educators, education institutions and government policy makers at large